2009
DOI: 10.1111/j.1600-0471.2008.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

« Un chef est un requin qui voyage par terre » : fonctions et statuts des armatures de projectile en dent de Carcharhinus leucas et aiguillon caudal de raie dans l’Arabie des VIe‐IIIe millénaires av. notre ère

Abstract: During the Neolithic and Early Bronze Age, many teeth of large sharks (Carcharhinus leucas) and stingray spines were transformed into projectile points in south‐eastern Arabia. These points were probably used for fishing. Deriving from dangerous and/or toxic animals, shark teeth and stingray spines were certainly markers of prestige.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…While drilled shark teeth are well attested during the Neolithic in Oman, the specimen found at Marawah is the only known example for this period in the Arabian Gulf. Charpentier et al () have suggested that single hole teeth were used as pendants rather than as projectile points, which is the case with the bi‐perforated teeth (Santini, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While drilled shark teeth are well attested during the Neolithic in Oman, the specimen found at Marawah is the only known example for this period in the Arabian Gulf. Charpentier et al () have suggested that single hole teeth were used as pendants rather than as projectile points, which is the case with the bi‐perforated teeth (Santini, ).…”
Section: Discussionmentioning
confidence: 99%
“…While drilled shark teeth are well attested during the Neolithic in Oman, the specimen found at Marawah is the only known example for this period in the Arabian Gulf. Charpentier et al (2009) have suggested that single hole teeth were used as pendants rather than as projectile points, which is the case with the bi-perforated teeth (Santini, 2002). The exploitation of a wide spectrum of small fish in shallow waters suggest the use of non-selective techniques such as beach seines and coastal barrier traps.…”
Section: Fishing Grounds and Techniquesmentioning
confidence: 99%
“…The study of traces and fractures of these teeth, together with a series of experiments carried out by archers, has shown that one is truly dealing with projectile points. One of them was moreover found stuck in the third lumbar vertebra of a human body of the Neolithic necropolis of Ra′s al‐Hamra 5 (Charpentier, Méry, Fortini, & Pellé, 2009; Fortini, 2012; Salvatori, 2007).…”
Section: Discussion: Sharks and Megaselachus Animals Which Were “Foomentioning
confidence: 99%
“…They were included in funerary spaces, by contrast with flint points, which were totally absent from graves. These points made from large predators were indeed a reflection of the skill required in the capture of dangerous animals, but their possession may also have been the sign of a certain prestige (Charpentier et al, 2009). Was the fossil of Sharbithat‐10 part of this set of tools embedded with a specific meaning?…”
Section: Discussion: Sharks and Megaselachus Animals Which Were “Foomentioning
confidence: 99%
“…Sharks are still a lucrative resource in the peninsula today, their flesh being dried or salted to be traded inland (Charpentier, ; ElMahi, ). Although few vertebrae have been found and published on coastal archaeological sites in Oman, it should be noted that Neolithic populations recovered shark teeth, and that some of them were transformed into arrowheads, a copy of which was found at SWY‐1 (Charpentier et al, ).…”
Section: Discussionmentioning
confidence: 99%